Effect of Filter Types on Physicochemical Properties, Volatile Compounds, and Sensory Evaluations of Purified Water by Point-of-Use Water Treatment - Mi-Ran Kim; JeongAe Heo; Sang Sook Kim; Eui-Cheol Shin; Chang Guk Boo; Han Sub Kwak (Foods, 2021)
This study investigated purified water from four different filter types for removing minerals, anions, and volatile organic compounds (VOCs), and affecting sensory perception and consumer acceptability. Ultrafiltration (UF), CSM-ultrafiltration (CU), alumina nanofiber (AN), and reverse osmosis (RO) filters were used for a point-of-use water treatment system with a pre-carbon filter (PR) and post-carbon filter (PO). Filters efficiently removed VOCs, which could negatively affect the sensory perception of water. The total VOC concentration of tap water (TW) (14.97 µg/Kg) was reduced by 70% by the PR, 75.3–88.7% by the PR-main filter, and >97% by the PR-RO-PR. Using the polarized sensory position test, the subjects clearly discriminated TW from the samples; however, most of the purified water was not. The difference in the mean ratings of consumer acceptability among the purified samples was <1 except for PR-RO-PO in consumer testing. These results suggested that although there are differences in the capability of different filter types to eliminate minerals, anions, and VOCs, overall consumers did not identify sensory differences among them, and demonstrated similar consumer acceptability of the purified water produced. Simply applying a pre-carbon filter for TW treatment is enough to minimize VOCs, which negatively influence consumer acceptability.